The role of teachers in enhancing the extrinsic motivation of grade X students at SMK Negeri 3 Rantau Utara - Uswatun Hasanah Rambe; Siti Zahara Saragih (Priviet Social Sciences Journal, 2023)
This research, conducted at SMK Negeri 3 Rantau Utara, illuminates the crucial role teachers play in elevating educational quality, specifically focusing on extrinsic learning motivation for Grade X students. Using a purposive sampling approach, the study engaged 1 teacher and 20 students to discern the broader implications of a teacher's role beyond traditional instruction. Findings highlighted teachers' dual capacities as "Educators" and "Innovators." As educators, they embed values, address academic challenges, and foster commendable communication. As innovators, they employ diverse, creative teaching methods, facilitating interactive sessions that stimulate student engagement and motivation. These dual roles underscore the transformative power of proactive teaching, revealing its potential to not only convey curriculum but to inspire and motivate, making learning a more enriching experience. The study underscores the need for an evolved teaching paradigm that goes beyond conventional methods to cultivate a truly engaging educational environment.